Pengaruh Fitur Live Streaming terhadap Keputusan Pembelian Produk Fashion pada TikTok Shop di Kalangan Mahasiswa Bandung Raya - Sheila Destian Dwi Fasya (International Journal Administration, Business & Organization, 2023)
The main aim of this study is to examine the influence of the live streaming feature on the purchasing decisions of fashion products on TikTok Shop among students in Bandung Raya, Indonesia. The research employs a quantitative descriptive method with a questionnaire as the data collection instrument. A total of 106 respondents, consisting of students from Bandung Raya, Indonesia with a history of purchasing fashion products on TikTok Shop, participated in this study. For data processing, this research utilizes frequency analysis, descriptive analysis, and simple regression. The research findings indicate that the live streaming feature significantly influences the purchasing decisions of fashion products on TikTok Shop among students in Bandung Raya, Indonesia by 74.3%, while the remaining 25.7% is influenced by other variables beyond the ones investigated